Determination of Anthocyanin at Different pH from Clitoria Ternatea sp. Using Maceration Method - Mohd Idris, Mohd Idris; Asman, Saliza; Aliea Suhana Abu Mohammad; Anis Faqehah Amirullah; Hafeeza Munira Mohd Tasyrif (Enhanced Knowledge in Sciences and Technology, 2024)
Clitoria Ternatea sp., popularly known as butterfly pea flower, is a popular ornamental plant with significant medicinal significance. Butterfly pea is also known for its bright blue colour, which can be used as a natural food colouring in sweets and beverages. In this study, anthocyanin was extracted using a maceration process with distilled water as the solvent. As a result, anthocyanin appears in purple, dark blue, and dark greenish hues depending on acidic, neutral, and alkaline pH. The UV-Vis spectrophotometer detected anthocyanin between 500 and 600 nm. The maximum absorbance of anthocyanin (8.50 A) occurs at pH 4, showing the presence of the highest concentration of anthocyanin in acidic conditions. The colour variations are caused by changes in anthocyanin’s structural arrangement, which result in the creation of petunidin, depinidin, and cyanidin.